Teleost fish IgM+ plasma-like cells possess IgM-secreting, phagocytic, and antigen-presenting capacities - Wu, Liting; Yang, Yanjian; Gao, Along; Li, Jun; Ye, Jianmin (Frontiers in Immunology, 2022)
Plasma cells are terminally differentiated antibody-secreting B lymphocytes that are responsible for humoral immunity by producing large amounts of antibodies. Increasing evidences suggest that teleost fish B cells share similar characteristics of mammalian B1 B cells, including antibody-secreting, phagocytosis and antigen-presentation capacities. However, the heterogeneity between mature B cell and plasma cells remains unclear. In this study, on the basis of light-scattering characteristics, we gated tilapia anterior kidney (AK) leukocytes as lymphoid (L) gate and granulocyte-monocyte/macrophage (G-M) gate, and discovered that there exists two IgM+ B cell subsets. IgM+ cell proportion and mean fluorescence intensity are higher in L gate than G-M gate, but with lower forward scatter and side scatter. Analyzed the morphological and ultrastructural features of sorted IgM+ cells: the L IgM+ cells presented high nucleus to cytoplasm ratio and the lymphocyte-like morphology, while the G-M IgM+ cells exhibit a small nucleus, more abundant endoplasmic reticulum and higher number of mitochondria and plasma-like or macrophage-like morphology. To further identify the cell types, the specific gene expression patterns related to B cell and T cell were examined, which demonstrated that B cell-specific genes expressed in the L IgM+ and G-M IgM+ cells, and the secreted IgM expressed extremely high in the G-M IgM+ cells surprisingly; however, T cell-related genes only expressed highly in L IgM- cells. These results imply that the G-M IgM+ cells are similar to plasma-like cells with high antibody-secreting capacity. Considering G-M is regarded including the granulocyte, monocyte and macrophage cell types but no B cells, monocyte/macrophage markers were used to investigate the cell types further, which showed that macrophage receptor with collagenous structure and macrophage-expressed gene-1 expressed highly in the G-M IgM+ cells. The phagocytosis in the G-M IgM+ is significantly higher than the L IgM+ cells when ingesting the beads or bacterium, and it is the same as antigen-processing capacity. Our findings indicate that tilapia AK possesses two IgM+ B-cell subsets, and the G-M IgM+ cell is resembled to plasma-like cell with high antibody-secreting, phagocytosis and antigen-presentation capacities, which provides better understanding of the functions of teleost fish plasma-like cells.